2011
DOI: 10.1007/s13580-011-0097-5
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of glucosinolates and nutrients in pakchoi (Brassica campestris L. ssp. chinensis var. communis) two cultivar plants exposed to sulfur deficiency

Abstract: To understand how sulfur nutrition affects the quality and yield of vegetable plants, we have grown two cultivars of pakchoi (Brassica campestris L. ssp. chinensis var. communis cv. Shang Hai Qing and You Dong Er) hydroponically in nutrient solution supplied with two levels of sulfur (0.0558 mM as sulfur deficiency and 1.0058 mM as sulfur sufficiency, respectively) for three weeks and their growth, nutrient uptake and glucosinolate content under these two sulfur conditions were investigated. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Experimental results indicated the marked role of S and Zn fertilization on sulforaphane accumulation in broccoli florets. Several reports also showed that S and Zn application can alter the concentration and composition of glucosinolates (GLS) in Brassica species (Hu et al, 2011;Sadeghzadeh, 2013). Schonhof et al (2007) found that S fertilization in combination with optimal N supply tended to increase the content of sulforaphane in broccoli florets.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results indicated the marked role of S and Zn fertilization on sulforaphane accumulation in broccoli florets. Several reports also showed that S and Zn application can alter the concentration and composition of glucosinolates (GLS) in Brassica species (Hu et al, 2011;Sadeghzadeh, 2013). Schonhof et al (2007) found that S fertilization in combination with optimal N supply tended to increase the content of sulforaphane in broccoli florets.…”
Section: Discussionmentioning
confidence: 99%